Hybrid Laminar Flow Control Optimizations for Infinite Swept Wings - Yayun Shi; Xiayu Lan; Tihao Yang (International Journal of Aerospace Engineering)
Maintaining the laminar flow on surfaces through active control is a significantly promising technique for reducing fuel burn and alleviating environmental concerns in commercial aviation. However, there is a lack of systematic parameter studies for the hybrid laminar flow control (HLFC) together with natural laminar flow (NLF). To address this need, we optimize the infinite swept wings with different sweep angles and at various conditions, including different Mach numbers, Reynolds numbers, and lift coefficients. The Reynolds-averaged Navier-Stokes (RANS) solver coupled with the linear stability theory is applied for the laminar-turbulent transition prediction, and the traditional optimization method based on evolutionary algorithms is applied for laminar flow wing optimization. The optimization results found that HLFC is required when the NLF fails at a larger sweep angle (35°) and Reynolds number (20×106). The lower pressure peak with boundary-layer suction is found to delay the transition of the regional aviation condition. Besides, the pressure distribution of HLFC is similar to NLF results at the lower Reynolds number (10×106) or sweep angle (25°), i.e., a gentle negative pressure gradient near the leading edge and a small favorable pressure gradient behind it. Clarifying the characteristics of laminar flow wings will advance the application of the laminar flow technique within its field.